Preparation of thiol-ene based photo-crosslinked polymer as a potential phase change material - KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2016)
A series of novel photo-crosslinked thiol-ene based shape-stabilized phase change materials (PCMs) have been prepared for the use of thermal energy storage applications. Four types of formulations were prepared with different fatty alcohols by adding di(trimethylolpropane) tetraacrylate (TMPTA), polyethylene (glycol) diacrylate (PEGDA) and pentaerythritoltetrakis(3-mercaptopropionate) (4-SH) in which we investigated their properties as shape-stabilized PCMs. Fatty alcohols, 1-Octadecanol, 1-Eicosanol and 1-Docosanol, were added to the formulations, respectively. The characterization tests were performed by ATR-FTIR spectroscopy. Phase change behaviors and thermal performances were investigated by using differential scanning calorimetry (DSC) and thermogravimetric analysis system (TGA).The heating cycle phase change enthalpy is measured between 27 and 43 J/g, and the freezing cycle phase change enthalpy is found between 20 and 39 J/g. The decomposition of UV-cured PCMs started at 413 degrees C.The results indicate that the photo-crosslinked thiol-ene based PCMs possess good phase change properties and have an applicable temperature range. With the obtained results these materials promise a great potential in thermal energy storage applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Polymers; Coatings; Thermal properties; Differential scanning calorimetry (DSC); FATTY-ACID EUTECTICS; THERMAL-PROPERTIES; HEAT-STORAGE; COMPOSITES; PCM; MICROCAPSULES; MORPHOLOGY; SYSTEM